The effect of acupressure on the quality of sleep in hemodialysis patients in Razi ‎hospital in ‎‏2007‏ - eisa nasiri; nasrin mokhtari; afsaneh ghanbari; zahra atr karruoshan (Guilan University of Medical Sciences, 2007)
Introduction: Sleep disorder is prevalent in hemodialysis patients. Treatments such as air way ‎positive pressure and medicines are not usually available or have side effects. Acupressure is a ‎non-invasive method from traditional Chiness medicine. It is proven useful in some studies in ‎treatment of sleep disorder.‎ Aim: This study surveyed the effect of acupressure on quality of sleep in hemodialysis ‎patient.‎ Material and Methods: This is a random clinical trial and sample consisted of ‎‏62‏‎ ‎hemodialysis patient who had sleep disorder. They were randomly divided into experiment ‎and control groups. The experimental group recived acupressure ‎‏3‏‎ times a week for four weeks ‎while they were under dialysis. The control group only received the routine treatment. The ‎quality of sleep was measured before and after intervention by pittrosburg sleep quality index. ‎Also sleep log was used to record the sleep pattern and finally descriptive and analytical ‎statistics, chi-square. Mannwitney, were used.‎ Results: Finding showed a significant difference between the experiment and control group ‎on quality of sleep based on pittrosburg sleep quality index and recovery in domain of ‎subjective quality of sleep (p=‎‏0.042‏‎), time needed to fall sleep (p=‎‏0.007‏‎), overall time of sleep ‎‎(p=‎‏0.017‏‎), habitual sleep efficiency (p=‎‏0.001‏‎), sleep disorder (p=‎‏0.024‏‎), daily activity ‎disorder (p=‎‏0.002‏‎) and overall score (p=‎‏0.0001‏‎). Also sleep log showed that overnight ‎sleeplessness decreased and patients' quality of sleep increased and this recovery started from ‎first week of intervention and continued up to one week after intervention.‎ Conclusion: this study indicated that acupressure promotes hemodialysis patients' quality of ‎sleep and it's a non-inasive treatment of sleep disorder in the patients.‎